Impacto dos países desenvolvidos e emergentes na economia brasileira - Bril, Marco (2013)
This dissertation compares the behavior of the Brazilian economy to emerging and developing markets through principal component analysis. There were used variables of economic growth, as PMI; and macroeconomic variables, such as inflation, stock exchange, currency and interest rates. To achieve more consistent results, there were done two different analyses. The first one has compared these variables from different countries to the Brazilian PMI; whereas the second one has separated the later analysis in different time periods, in order to differentiate the period before and after the 2009 crisis.